Empowering lives and industries : Tech-driven solutions for accessibility, logistics and entrepreneurship - Harum, Norharyati (Penerbit UTeM Press, 2025)
Empowering Lives and Industries: Tech-Driven Solutions for Accessibility, Logistics and Entrepreneurship is a collection of articles from the Conference on Business, Social Science, and Technology 2024 (CoNeSCINTech 2024). It showcases how technology is used to break barriers and boost innovation in business and society. The book emphasizes the practical application of tech to enhance lives and operations across various sectors. Through five chapters, it presents diverse projects tackling real-world challenges using advanced technology. Each contribution reflects the conference's goal of merging innovation with impactful solutions.